Pengaruh Profitabilitas Terhadap Nilai Perusahaan Dengan Kebijakan Deviden Sebagai Variabel Intervening - Lutfiyatul Izzah; Achmad Zaki (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research examines dividend policy and company value and profitability. The population studied included 57 banking companies listed on the Indonesia Stock Exchange from 2018 to 2021. This research selected ten banks using purposive sampling. The SPSS version 24.0 program was used to conduct multiple linear regression studies. Based on the findings of this research, the value of a company increases in part by Profitability and Dividend Policy. Profitability growth increases company value but has little influence on dividend policy. Dividend policy reduces the impact of profitability on company value by 1.28 percent. Keywords: Company Value, Dividend Policy, Profitability